Pathological findings of severe pancreatolithiasis in a cow - NOURANI, H.; JAFARI DEHKORDI, A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this study was to describe macroscopic and microscopic characteristics of pancreatolithiasis in a cow. On post mortem examination, severe pancreatolithiasis or a large numbers of white stones with rough surfaces and the ectasis of pancreatic ducts were observed in a female dead cow. Histopathological examination of the affected pancreas revealed focal dilation of exocrine pancreatic acini, atrophy of the acini epithelial cells, infiltrations of lipocytes, mild cystic dilatation of the glands, squamous metaplasia and infiltration of chronic inflammatory cells in the pancreatic ducts wall. The histopathological results of this study showed that pancreatolithiasis can cause microscopic changes in the affected pancreas that some of these lesions have not previously been reported in pancreatolithiasis. Further studies are needed to find out the effects of these microscopic changes on the gland functions in cow.